Using autolyzed and dried Saccharomyces cerevisiae as various macromolecules and sucrose substitute: Developing novel gummy - Elobeid, Tahra; Tuzun, Burcu; Apaydin, Ayse; Toker, Omer Said; Doguer, Caglar; Palabiyik, Ibrahim; Aksu, Muhammed Irfan; Konar, Nevzat; Atalar, Ilyas (ELSEVIER, 2025)
Autolyzed yeast cells contain a combination of various macromolecules such as mannan oligosaccharides, glucans, and manno protein, and they are noteworthy as a source of prebiotics and postbiotics. This study used spray drying to obtain Saccharomyces cerevisiae autolyzed yeast cells powder and replaced it with sucrose in a gummy formulation. The increase in the amount of autolyzed yeast also caused a significant increase in the total phenolic contents and antioxidant capacity. The optimum points for gummy ingredients were 26.27 % sucrose, 6.33 % autolyzed yeast cells, and 7 % gelatine concentrations, considering maximum springiness, bioactive properties, and minimum springiness, hardness, and Delta E changes during accelerated shelf-life storage. Optimum gummy formulation significantly reduced Caco-2 (55 %) and A549 (60 %) cell viability compared to the control group. It was concluded that yeast cells-added gummies could be a healthy substitute and could be commercialized due to their acceptable structural and sensorial properties.
Keywords: Autolyzed yeast cell; Bioavailability; Gelatine; Gummy; Confectionery; ANTIOXIDANT PROPERTIES; BETA-GLUCAN; SHELF-LIFE; CELL-WALL; CLASSIFICATION; MOISTURE; GRAPE; Chemistry; Food Science & Technology